2017
DOI: 10.3390/economies5040039
|View full text |Cite
|
Sign up to set email alerts
|

Does Foreign Direct Investment Harm the Environment in Developing Countries? Dynamic Panel Analysis of Latin American Countries

Abstract: Abstract:This article sets out to study the FDI-environment nexus within a dynamic panel data framework. To that end, the pooled mean group (PMG) method of Pesaran et al. (1999) is used to assess the impact of FDI on CO 2 emissions, controlling for income and energy consumption, using a panel of 17 Latin American countries. Our results using the full sample show that FDI increases CO 2 emissions, confirming the pollution haven hypothesis. But when splitting the data into different income groups, FDI inflows on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
3
20
0
Order By: Relevance
“…For example, a 1% increase in energy consumption increases CO 2 emissions by approximately 0.973% (0.619%) in the long (short)-run, holding income fixed. This further suggests that as found in previous studies (e.g., Iwata et al 2011;Baek and Choi 2017), energy consumption is one of main determinants in determining CO 2 emissions in Kazakhstan and should be accounted for when estimating the income-environment nexus accurately.…”
Section: The Resultssupporting
confidence: 67%
“…For example, a 1% increase in energy consumption increases CO 2 emissions by approximately 0.973% (0.619%) in the long (short)-run, holding income fixed. This further suggests that as found in previous studies (e.g., Iwata et al 2011;Baek and Choi 2017), energy consumption is one of main determinants in determining CO 2 emissions in Kazakhstan and should be accounted for when estimating the income-environment nexus accurately.…”
Section: The Resultssupporting
confidence: 67%
“…The findings of the study revealed the validity of PHH and environmental Kuznets curve (EKC) not only for the full sample but also for high-and lowincome countries. Baek and Choi (2017) found that FDI increases CO2 emissions and confirmed the validity of PHH in 17 Latin American economies for the time period of 1971-2011. The research divided the sample into low-, middle-and high-income countries but the positive impact of FDI on CO2 emissions was only confirmed in high-income countries.…”
Section: Review Of Literaturesupporting
confidence: 62%
“…Study on the relationship between per capita income and environmental degradation has been undertaken by many researchers (Baek & Choi, 2017;Dinda, 2004;Sehar & Khan, 2013;Shahbaz, Dube, Ozturk, & Jalil, 2015) who modeled through the Kuznets Environment Curve hypothesis (EKC) which was first introduced by Grossman & Krueger (1991) on the study of potential impact of NAFTA. According to the Environmental Kuznets Curve hypothesis in the early stages of economic growth, environmental degradation and pollution are increasing but at certain per capita income levels the trend is reversing.…”
Section: Introductionmentioning
confidence: 99%